2013
DOI: 10.1002/asi.22760
|View full text |Cite
|
Sign up to set email alerts
|

New patterns of scientific growth: How research expanded after the invention of scanning tunneling microscopy and the discovery of Buckminsterfullerenes

Abstract: This article describes patterns of scientific growth that emerge in response to major research accomplishments in instrumentation and the discovery of new matter. Using two Nobel Prize‐winning contributions, the scanning tunneling microscope (STM) and the discovery of Buckminsterfullerenes (BUF), we examine the growth of follow‐up research via citation networks at the author and subdiscipline level. A longitudinal network analysis suggests that structure, cohesiveness, and interdisciplinarity vary considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…The methodological distinction between research breakthroughs and follow-up research was introduced by Heinze et al [ 59 ], who studied growth patterns of publications that cited two Nobel Prize–winning contributions in chemistry and physics. They focused on all publications that cite the papers in which these two particular research breakthroughs were first published.…”
Section: Methodsmentioning
confidence: 99%
“…The methodological distinction between research breakthroughs and follow-up research was introduced by Heinze et al [ 59 ], who studied growth patterns of publications that cited two Nobel Prize–winning contributions in chemistry and physics. They focused on all publications that cite the papers in which these two particular research breakthroughs were first published.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research suggests that collaboration leads to increased productivity and is understood as necessary for successful research and relevant for receiving funding (Heinze, Heidler, Heiberger, & Riebling, 2013;Iglič, Doreian, Kronegger, & Ferligoj, 2017;Katz & Martin, 1997;Melin & Persson, 1996;Tsai, Corley, & Bozeman, 2016;Wray, 2002). Researchers perceive publishing together easier, because they can exchange ideas and get feedback within teams more quickly than as single author (Gordon, 1980;Lewis, Ross, & Holden, 2012;Metz & Jäckle, 2017;Tsai et al, 2016).…”
Section: Collaboration Types In Academiamentioning
confidence: 99%
“…Van Dalen and Henkens (2005) investigated tell-tale signals of later citation activity, in the field of demography, one of which was whether the state of uncitedness negatively impacted a paper's potential citation at a future time ("negative duration dependence"), and concluded that it was far from the "death sentence" common wisdom considered it to be, but a study by Li et al (2014) found that the length of sleep (i. e., uncitedness or very low citation activity) did correlate with lower probability of later awakening. Similarly, in a larger study on delayed recognition focusing onlyon highly cited papers, Glänzel, Schlemmer and Thijs (2003) found that delayed reception did not simply "shift" the citation process in time, and that belated citation activity came with higher risk of uncitedness. Levitt and Thelwall (2008) studied late citation to determine indicators that might predict the presence of (future) highly cited papers.…”
Section: Introductionmentioning
confidence: 95%